Impact of salinization and pollution of groundwater on the adaptation of mosquito vectors in the Jaffna peninsula, Sri Lanka - Surendran, S.N.; Senthilnanthanan, M.; Jayadas, T.T.P.; Karunaratne, S.H.P.P.; Ramasamy, R. (My University, 2020)
Mosquito-borne diseases are a major health concern in many tropical and sub-tropical countries. In the absence of specific treatment for many mosquito-borne diseases, vector control in the form of eliminating preimaginal development sites and insecticide application has an important role in controlling these diseases. Anthropogenic environmental changes have become important driving forces causing the adaptation of many major mosquito vectors to such changes. Anthropogenic activities are major contributors to global warming that is causing arise in sea levels. Sea level rise along with over exploitation of groundwater results in sea water intrusion to fresh water aquifers causing fresh water salinization in coastal zones. Human activities, including the extensive use of fertilizers and agrochemicals, also cause groundwater pollution. Mosquito vectors that normally lay eggs and undergo preimaginal development in fresh water are now seen to be adapting to develop in brackish and polluted water habitats. This article reviews recent findings that show the adaptation of mosquito vectors of human diseases to lay eggs and undergo preimaginal development in groundwater that is undergoing rapid salinization and pollution in the Jaffna peninsula.
Keywords: anthropogenic environmental changes; groundwater pollution; Jaffna peninsula; mosquito adaptations; mosquito range expansion; mosquito vector-borne diseases; salinization of groundwater